Effects of Sc and Zr on the texture and mechanical anisotropy of high strength Al - Zn - Mg alloy sheets - Deng, Y.; Yin, Z.M.; Xu, G.F.; Wang, Y.J.; Lu, L.Y.; Duan, J.Q. (Проблемы прочности, 2016)
Texture, mechanical anisotropy and microstructure of aged Al–Zn–Mg, Al–Zn–Mg–0.1Sc–0.1Zr and Al–Zn–Mg–0.25Sc–0.1Zr (wt.%) alloy sheets were investigated by tensile tests and electron microscopy. Sc and Zr additions do not change the texture of homogenized and cold rolled alloys, but transfer the cube texture of the aged Al–Zn–Mg alloy into -fiber rolling texture. With increasing Sc and Zr additions, the strength significantly increases, and mechanical anisotropy is enhanced. The strength is highest parallel to the rolling direction, whereas it is lowest at a 45° angle to the rolling direction. The higher strength is mainly due to grain boundary strengthening and precipitation strengthening caused by Al₃ScxZr₁₋x nano-particles. The stronger mechanical anisotropy is ascribed to the rolling texture, due to the inhibitory effect of Al₃ScxZr₁₋x on recrystallization. A new model was successfully established to reveal the interrelation between Sc and Zr additions, texture and yield strength anisotropy of Al–Zn–Mg sheets.